Toughening mechanisms in particulate dental resin-based composites : a short review - Kundie, Fathie; Zainal Arifin Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Resin-based composites represent a unique class of restorative dental materials; however, these composites have severe shortcomings such as low wear resistance which is mainly responsible for the short life-span of the materials. Composites characteristics such as strength, stiffness, resistance to abrasion, polymerisation shrinkage, thermal expansion coefficients and moisture absorption depend on the filler particles and coupling agents used. Fortunately, these composites have been the focus of attention for numerous researches in recent years which aim to improve the performance of the restorations in several ways. Using several types of coupling agents, and different particle sizes and types have gained the great interest of researchers. The latter plays a critical role in the toughening mechanisms in resin-based composites. Therefore, the purpose of this review is to discuss the literature regarding the toughening mechanisms in particulate dental resin composites since these mechanisms are also crucial factors for the improvement of mechanical properties. The four main types of toughening mechanisms discussed are: crack deflection, pinning, bridging and particle-matrix interface. The current review indicates an improvement in mechanical properties of particle-filled dental composites due to the presence of various toughening mechanisms. The dental resin composites’ fracture toughness is mainly contributed by crack deflection, pinning and bridging that take place in micro- and nanocomposites, in addition to the hybrid composites. Filler–matrix interphase plays an important role in improving the mechanical properties, in addition to its positive effect on crack deflection and bridging. In reality, all these mechanisms could occur simultaneously at different intensities, respectively.